Analisa SWOT 8 SNP untuk Perbaikan Mutu Madrasah di MTs Khaudlul Ulum Penajung - Afifatun Nahriyah; Akhmad Dwi Riyanto; Hertri Pertiwi Palupi; Kharisatur Rokhmah; Agus Salim Chamidi (Ar-Rihlah: Jurnal Inovasi Pengembangan Pendidikan Islam, 2022)
8 national standards of Education (SNP) are standards that must be held in madrasah. However, in its implementation is generally less than the maximum note the strengths and weaknesses as well as the opportunities and challenges of each. This study aims to comb one by one 8 SNP, both strengths, weaknesses, opportunities, and challenges, then summarize them in making work priorities for improving the quality of madrasah. The method used is SWOT analysis, with data collection techniques in the form of interviews, observations, and documentation of about 8 SNP. The informants of the study were the head of the madrasah and a number of teachers and related staff. The management theory used is quality management and plan-do-check-act (PDCA). Research begins October 20, 2022. The results of the study were: (a) principals make planning decisions facilities and infrastructure in MTs Khaudlul Ulum. (b) MTs Khaudlul Ulum has limited infrastructure so that in the application of 8 national standards of education is not maximized on each indicator. (C) the evaluation allocates several rooms to be used as classrooms. (d) the principal's efforts in taking action is to plan RAB one year ahead.